2013
DOI: 10.1136/archdischild-2012-303045
|View full text |Cite
|
Sign up to set email alerts
|

Trends in body mass index distribution and prevalence of thinness, overweight and obesity in two cohorts of Surinamese South Asian children in The Netherlands

Abstract: The low mean BMI Z-score and high prevalence of thinness are likely expressions of the characteristic body composition of South Asians. Universal BMI cut-offs should be applied carefully in South Asian populations as thinness prevalence is likely to be overestimated and obesity underestimated. The development of ethnic specific cut-offs is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…In the current study, the mean BMI z-score of Surinamese South Asian children was even the lowest of all ethnic groups, and overweight (including obesity) prevalence was at 17% only slightly higher than in Dutch children. Nonetheless, the prevalence rates in Surinamese South Asian children may not represent the true prevalence in this group, as we recently showed that current universal cut-offs to determine overweight and obesity are likely to be too high for South Asian children 14. Consequently, the current overweight and obesity rates in South Asian children expectedly underestimate the true prevalence in this group.…”
Section: Discussionmentioning
confidence: 86%
“…In the current study, the mean BMI z-score of Surinamese South Asian children was even the lowest of all ethnic groups, and overweight (including obesity) prevalence was at 17% only slightly higher than in Dutch children. Nonetheless, the prevalence rates in Surinamese South Asian children may not represent the true prevalence in this group, as we recently showed that current universal cut-offs to determine overweight and obesity are likely to be too high for South Asian children 14. Consequently, the current overweight and obesity rates in South Asian children expectedly underestimate the true prevalence in this group.…”
Section: Discussionmentioning
confidence: 86%
“…However, the under-five mortality is almost half that of Sub-Saharian Africa [24]. Furthermore, in affluent Surinamese South Asian children living in the Netherlands, a disproportionately high prevalence of thinness was found [25]. This is likely to be a consequence of the high body fat percentage at low BMI, resulting in many ‘underweight’ children being misclassified.…”
Section: Introductionmentioning
confidence: 99%
“…For children, between 5-17 years in this regional prevalence data on overweight and obesity are currently unavailable [3]. However, data for overweight and obesity prevalence among children in different countries in South Asia are available: 25.0% among children from 2 to 15 years in Bangladesh and 22.0% among children from 5 to 19 years in India.…”
Section: Introductionmentioning
confidence: 99%